Virtual reality-based learning digitization in disaster education for students in disaster-prone schools in Banggai district - Enteding, Almustar; Otoluwa, Anang S.; Tongko, Mirawati; Pomalango, Zulkifli B.; Lahay, Fahrudin; Dee, Mustakim La (Edelweiss Applied Science and Technology, 2025)
Indonesia is a zone that has a high level of disaster potential because it is included in the ring of fire so that disaster events are at high risk which requires community preparedness to face all possible events. Banggai District of Central Sulawesi Province is a disaster-prone area based on GIS (Geogrpahycs Information System). In the last 5 years, Banggai Regency has been hit by earthquakes, hurricanes and floods with a distribution of disaster-prone areas scattered in 19 disaster-prone sub-districts with a total hazard area of 81,632 hectares. For this reason, disaster management programs are a priority for the local government. Disaster management can be done through disaster education intervention as early as possible in the school setting, but the learning process needs to be improved to be more innovative and effective, one of which is through the virtual reality-based Audio-Visual learning digitization method. The purpose of this research is to design learning innovations towards virtual reality-based digitalization in disaster education at the school level. This research uses the Mix Method approach.